THE EFFECT OF ESG AND CAPITAL STRUCTURE ON FIRM VALUE IN ASEAN-5 - Irma Rahma Utami; Eduard Ary Binsar Naibaho (Proceeding National Conference Business, Management, and Accounting (NCBMA), 2026)
The research is driven by the increasing demand for sustainable finance and the inconsistency of previous findings in emerging markets. This quantitative study addresses heteroskedasticity and cross-sectional correlation using panel data regression with Driscoll-Kraay Standard errors. A total of 1,070 observations for 2015-2024 are generated by the sample, which includes 107 non-financial companies in five ASEAN-5 countries. The t-test results indicate that the influence depends on the firm value proxy used. ESG and DER were not statistically significant in Model 1 (Tobin's Q). Nevertheless, PBV was significantly and positively impacted by both primary variables in Model 2 (PBV). The regression model (F-test) was statistically significant overall. These results suggest that the ASEAN-5 capital market is highly responsive to ESG and optimal debt usage (DER) when value is measured by PBV, which is consistent with both the Trade-off Theory and the Stakeholder Theory. The implication is that management is encouraged to prioritize ESG investments strategically, as these have been shown to improve market valuation (PBV) substantially.